Teaching Language and Cultural Creativity through the Textual Composition of the Hispanic American Tale Epistemological Reasoning and Subjective Imagination (Global Journal of Human-Social Science, 2023)
Currently the search for alternatives that allow the teaching of creativity is subject of discussion in the scientific research community Due to the attention that this is having in the educational field including the discipline of Spanish as foreign language ELE it is necessary to provide new approaches and possible solutions that cope with this view The objective of this research is to present a manuscript that serves as a reference for the teaching Spanish language and cultural creativity through the textual composition of the Hispanic American Tale To achieve this objective an analysis of this theme has been carried out in juxtaposition with the hypothesis that the research presents The result of which straits the acquisition of cognitive and affective domains of the target language The research has used a combined qualitative and quantitative method for the collection and analysis of literary materials from the hand and work of prominent Hispanic American writers scientific and academic publications and accredited websites This documentation is in absolute correspondence with the objective presented in this research study
Keywords: creativity; short story; spanish as foreign language; cognitive and affective domains; teaching and learning